Effect of different allocation methods on LCA results of products from wild caught fish and on the use of such results. - Svanes, Erik (The International Journal of Life Cycle Assessment)
Purpose The purpose of this study has been to investigate the effect of different allocation methods on life cycle assessment (LCA) results of products derived from line caught cod and the consequences of applying these methods considering the main aims of this case study. These aims were for internal improvement work and communication of results to the market. Methods Standard LCA methodology was applied. Mass allocation, economic allocation, a novel hybrid allocation and gross energy content allocation have been tested on a case study, and the results are discussed. In the case study, allocation problems in the studied case arose in the fishing and processing stages. Avoidance of allocation by splitting of processes, biological causality and system expansion or the avoided product approach was deemed to be not feasible. Results and discussion Economic allocation gave a much larger spread of impacts between the different products than mass allocation, especially for processing residue, due to large price differences. Hybrid allocation gave impacts in between mass and economic allocation because the set factors give a higher value for products that are for human consumption. Energy allocation gave results close to mass allocation because the energy content is quite similar in different species and products. Economic allocation is sensitive to price changes, the others are not. When used for evaluating environmental performance improvement measures that change the relative yields for human consumption and other purposes, the different methods used reflected very different results. When used in communication to the market, the different allocation methods yield results that could lead to different behaviours by market actors. Conclusions The different allocation methods gave very different results for the studied products; hence in order to achieve comparability between products, the same method must be used in all the cases. Different allocation methods might be appropriate for different purposes. For external communication to the market, mass allocation might be the preferred method in most cases. For internal improvement work, both economic and mass allocation could be used, but economic allocation might be the best alternative. The comparability of LCA results of products from wild caught fish is limited, due to the lack of an agreed standard method. It is recommended to consider the different applications of the results when developing such a method. Different purposes might require different methodological choices, e.g. allocation methodology.